Newborn screening for congenital hypothyroidism in a tertiary care centre - Seeralar A. T., Arasar; J., Ganesh; S., Padmanaban (International Journal of Contemporary Pediatrics, 2016)
Background: Congenital hypothyroidism (CH) is one of the most common preventable causes of mental retardation in paediatric population. Universal screening though possible is still not available for neonates even in tertiary care centers because of low priority in spite of proven community benefits. The aim and objective was to determine the prevalence of CH in neonates in a tertiary care center. Methods: The study was conducted in the neonatal unit of RSRM Lying in hospital- Stanley medical College as a prospective cross sectional study from March 2012 to May 2012. All newborns with gestational age of 34 weeks or more delivered in the hospital were included in the study. Sample was collected after getting informed consent after 48 hours of age till 7 days of age. 1695 babies who met the inclusion criteria were enrolled, from whom sample was collected. The blood sample was collected by heel prick on to a filter paper and TSH levels estimated by dissociation enhanced lanthanide fluorescent immunoassay (DELFIA). Exclusion criteria were preterm infants with gestational age less than 34 weeks, those who have received blood transfusion prior to sampling, neonates more than 7 days of age and refusal of informed consent were excluded from the study. Results: The study population consists of 1695 newborns. Among 1695 newborns 3 babies had elevated TSH representing a prevalence of 1.7 per 1000. Conclusions: Our Study results revealed the prevalence of hypothyroidism among infants is 1.7 per thousand.